Cystic fibrosis transmembrane conductance regulator in the gills of the climbing perch, Anabas testudineus, is involved in both hypoosmotic regulation during seawater acclimation and active ammonia excretion during ammonia exposure - Ip, Y.K. (2014)
10.1007/s00360-012-0664-9